Late Viking-Age Dragon-Slayers — Two Unusual Urnes-Style Brooches from Sjælland, Denmark. - Pedersen, Anne; Oehrl, Sigmund (Medieval Archaeology, 2021)
IN 2003 AND 2007, TWO UNUSUAL VIKING-AGE BROOCHES were discovered during metal-detector surveys on Sjælland (Zealand), Denmark. The brooches depict a horseman killing a serpent-like animal with his spear. The stylised beast is clearly associated with the Urnes style, dating to c ad 1050–1100, and the meaning of the motif is discussed in the context of early medieval dragon-slayer narratives and imagery. The acceptance and transformation of Classical and Byzantine iconographic traditions of equestrian saints has a long history in continental Germanic and Scandinavian art. In the Migration and Merovingian periods these images were incorporated into a pagan iconography, but the Urnes style was used in contexts which were definitively Christian, and it is possible that the two Danish brooches represent a very early depiction of Saint George in Scandinavia. Together with other finds, they add new perspectives to our understanding of the adoption of Christian iconography and narratives in Scandinavia.